Arctic sea ice in the light of current and past climate changes - I. I. Borzenkova; A. A. Ershova; E. L. Zhiltsova; K. O. Shapovalova (Лëд и снег, 2021)
Data from satellite observations (1979–2020) showed that over the last 40 years, years with a decrease in the area of summer ice extent and their thickness have prevail. Over 10 years, negative trends in anomalies of ice area and thickness of the ice are −13 and −15%, respectively. There is also a rapid reduction in the area of old ice (> 4 year-old): while in 1985 it was estimated at 2.7 million km2 while in March 2010 it was 0.34 million km2 . The paper analyses paleo-sea ice extent during the Holocene (the last 12,000 years) based on empirical biomarkers IP25 (a sea ice proxy with 25 carbon atoms synthesized by the specific Arctic sea ice diatoms Haslea spp. which have been proven to be a suitable proxy for paleo-sea ice reconstructions) obtained from deep-sea cores from the North Atlantic. The data obtained showed that during the warm periods of the Early and Middle Holocene, the area of summer sea ice was reduced to a minimum. This confirms the conclusion made earlier in [28] that the current trend of reducing the area and thickness of ice is unprecedented over the past 1,500 years. There is no complete analogue of the climate in the past corresponding to the current level of the CO2 concentration in the atmosphere. The closest time interval in terms of CO2 content is the warming of the Middle Pliocene between 3 and 4 million years ago, when the CO2 content in the atmosphere was 450–500 ppm against approximately 420 ppm at present. Paleo-climate reconstructions for this period estimate the global temperature to be 3.0–3.5±0.5 °C higher than at the end of the 19th century. Summer air temperatures in the high latitudes of the Northern Hemisphere exceeded the current ones by 8–10 °C, and the sea ice in the Arctic shelf seas was completely absent in the summer. Empirical data and model simulations have shown that presently the main driver of the reduction of the Arctic sea ice area is the increase in concentration of CO2 in the atmosphere. At the present time old sea ice tends to be replaced by seasonal ice demonstrating natural shift from predominance of permanent ice to the ice-free Arctic. In case of continuous increase in CO2 concentration in the atmosphere despite the emission control measures, one of the scenarios, which had happened in the past, may come true.